The Relationships Among Atherogenic Index of Plasma and Carotid–Femoral Pulse Wave Velocity in Adults - Xiaowen Ou; Tong Lin; Jin Gong; Xiaoqi Cai; Ying Han; Guoyan Xu; Liangdi Xie (The Journal of Clinical Hypertension)
ABSTRACT The relationships between the atherogenic index of plasma (AIP) and carotid–femoral pulse wave velocity (cfPWV) in adults were investigated. A total of 1398 subjects were included according to the inclusion criteria. Demographic data, medical history, and biochemical indicators were collected. The cfPWV was measured using the Complior Analyse device. AIP was calculated using the following formula: AIP = log (triglycerides/high‐density lipoprotein cholesterol). Correlation analysis, multiple linear regression, and logistic regression were performed to explore the relationships between AIP and cfPWV. Compared to the cfPWV normal group, the cfPWV elevated group had a higher level of AIP (p < 0.05). In all subjects, mild‐to‐moderate correlations were found between AIP and cfPWV (p < 0.05). Stepwise multiple linear regression analysis revealed that AIP was an independent factor associated with cfPWV (β = 0.156, p < 0.05). Logistic regression analysis indicated that the prevalence of cfPWV ≥ 10 m/s increased with the rise of AIP (OR = 18.291, p < 0.05). The ROC curve analysis showed that the area under the curve for AIP was 0.697. The critical point for AIP was determined as 0.00 by the Youden index (sensitivity of 76.2% and specificity of 54.3%). Stepwise multiple linear regression analysis showed that in the young and middle‐aged group with normal cfPWV, AIP was an independent factor associated with cfPWV (p < 0.05). In adults, AIP is an independent factor associated with an increased cfPWV. When AIP > 0.00, it has a certain predictive value in the screening of atherosclerosis.